Location-based Social Network for Cities & Neighbourhood Sustainable Development - Wan Zamry, Wan Nor Adilah (Universiti Teknologi PETRONAS, 2011)
Online Social Network (OSN) is categorized as Web 2.0 which is defined by O'Reilly in 2004, is the idea of mutually maximizing collective intelligence and added value for each participant by dynamic information sharing and creation. Current trend sbows that the next big thing in OSN is Location-based Social Networking (LBSN) which is the composite of OSN and Location-based Service (LBS). The goal of this paper is to study on Malaysian online social behaviour and to explore what are the key technologies of LBSN to support the development of neighbourhoods where residents feel a sense of connection to their local community and ability to engage in that community. Problems and opportunities identified are: I) Lack of research has been done to nnderstand Malaysian online social behavior in the context of cities & neighbourhood development, 2) Modem societies are said to lives in a condition of individualism and 3) Malaysia has strong networked community and there are a number of social Application Programming Interface (API) which provide a great opportunities for developers to create an application which can support the idea of smart, liveable and sustainable cities. The objectives of the research are: 1) To study on Malaysian social behavior in using Location-based Social Network (LBSN) , motivation for participation and pattern of use, 2) To identifY and understand key technologies of LBSN, and 3) To design an engaging LBSN which leverage on key technologies for neighbourhood and cities' sustainable development. Survey instrument is used as data collection tool to investigate the Malaysian online social behaviour and gauge their views on civil issues such as crime in their residential. Interview also is carried out to the owner of existing crime mapping system to identifY the gaps and opportunities for improvements. This research discovers that Malaysians are socially active in online community network and have strong civic conscious to make our neighbourhood works better. Govermnent shonld look forward into open data for beneficial of public. With proper neighbourhood planning, it will contribute to sustainable community which can help country's development.